Perbedaan Pengetahuan Remaja Putri Sebelum Dan Sesudah Diberikan Edukasi Gizi Seimbang Dengan Media Video Di Posyandu Remaja - Agustini, Ni Made; Astiti, Ni Komang Erny; Armini, Ni Wayan (AKADEMI KEBIDANAN DHARMA HUSADA KEDIRI, 2024)
Background: Frequent adolescent nutritional problems include chronic energy deficiency and anemia. CED and anemia in adolescent girls cause various health problems which can increase the risk of anemia during pregnancy. Objective: This study aims to determine the difference in knowledge of young women before and after being given balanced nutrition education using video media at the youth posyandu in the Kediri III Community Health Center area. Method: This research was pre-experimental with a one group pretest-posttest design with a sample size of 41 respondents. The research was carried out at the youth posyandu in the working area of ​​Kediri III Community Health Center from February to March 2024. The sampling technique used was cluster random sampling technique with a sample size of 15 young women in Bengkel Village, 16 in Pandak Gede Village, 10 in Belalang Village. Median The pretest was 60, the median posttest was 85, so the median difference was 25. Results: The results of the Wilcoxon test analysis showed a p value of 0.000<0.05. The positive rank value in this study was 41, meaning that all respondents experienced an increase in knowledge after education. Conclusion: The conclusion of this research is that there are differences in the knowledge of young women before and after being given health education about balanced nutrition using video media. Suggestions: We recommend that innovative efforts be made in implementing youth posyandu activities using media such as videos so that they can foster youth interest according to their age and needs. Keywords: Anemia; Balanced Nutrition; Chronic Energy Deficiency; Young Women